Risco osteomioarticular relacionado ao trabalho doméstico - Domingos, Patricia (Universidade Federal de São Carlos, 2016)
The Musculoskeletal Diseases (WMSDs) related in this work have been discussed for years in Brazil, but, still cause major problems throughout life of many workers. According to the literature, the housekeepers have no access to adequate security measures within your work environment and there is a lack of supervision and control of this condition. Furthermore, occupational diseases related to domestic work remain neglected. Aiming to identify risk factors for develop musculoskeletal disorders related to domestic work, it was observed the daily work of a housekeeper during a whole working day. The most common were formed by poor posture, many movements with flexion of the spine, prolonged standing positions, poor organization of work and lack of adequate guidance to the employee about these issues. Therefore, it is important the creation of preventive measures to minimize the occurrence of musculoskeletal disorders related to domestic work. In this paper, the researcher highlighted the importance of preventive physiotherapy in improving working conditions in such activities.
Keywords: Saúde; Doenças osteomusculares; Trabalho doméstico; CIENCIAS DA SAUDE